PHOTODEGRADATION AND ANTIOXIDANT ACTIVITY OF CHLOROPHYLL a FROM SPIRULINA (Spirulina sp.) POWDER - Rebecca Christiana; Hari Kristopo; Leenawaty Limantara (Universitas Gadjah Mada, 2008)
Research on chlorophyll a from Spirulina (Spirulina sp.) powder has been done in order to determine chlorophyll a content, to compare degradation pattern and kinetics degradation of chlorophyll a and crude extract as well as to investigate the difference of antioxidant activity of chlorophyll a with or without irradiation. Chlorophyll a content in spirulina powder was calculated by using Porra's equation. Irradiation and recovery ability of chlorophyll a were measured by using volpi light (Intralux 6100) equipped with daylight filter. The antioxidant activity of chlorophyll a was determined by using DPPH method. The results showed that chlorophyll a content was 2.886 μg/g dry weight. Chlorophyll a has the higher stability than crude extract against 60 minutes irradiation at room temperature. Kinetics degradation of chlorophyll a was based on second order while crude extract based on first order. Chlorophyll a and crude extract have recovery ability. The results also showed that antioxidant activity of chlorophyll a was increased after 60 minutes of irradiation.